Retinal necrosis as the initial presentation of primary intraocular lymphoma - Majumder, Parthopratim Dutta; Raghothaman, Nirupama; Kharel, Ranju; Kumar, Nitin; Khetan, Vikas (Nepalese Journal of Ophthalmology, 2017)
A 72 years old female presented with bilateral painless progressive loss of vision over one year. She was diagnosed as non-resolving bilateral panuveitis. Her visual acuity in right eye was hand movement close to face and left eye was perception of light with inaccurate projection of rays. Bilateral anterior chamber had 1+ cells and flares. Vitreous cells had 1+ cells and haze in right eye but the left eye had 3+ vitreous cells and haze. Right eye fundus had multiple, discrete sub retinal yellowish deposits with subretinal haemorrhage and macular edema with perivascular infiltrates. In left eye, disc was just visible. The patient underwent diagnostic vitrectomy in left eye and undiluted vitreous sample on cytology showed reactive large lymphoid cells with necrotic background pattern suggestive of intraocular lymphoma. Patient underwent external beam radiotherapy and chemotherapy.